Sparsification of Compact Ultrametrics - Nykyforchyn, Oleh; Penhryn, Volodymyr (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2026)
We introduce and study a relation of refinement between compact ultrametrics. Efficient methods to determine ultrametrics by functions on binary trees and by symmetric bilinear forms that attain a diagonal form in a basis of Haar-like wavelets, are also proposed.